PEMBERDAYAAN PEKERJA TAMBAK DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA DI DESA BARU-BARU TANGA KECAMATAN PANGKAJENE KABUPATEN PANGKEP (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This research was conducted to determine the form of empowerment of tambak workers in improving family welfare in Baru-Baru Tanga Village, Pangkajene Subdistrict, Pangkep Regency and to find out how the constraints of farmworkers in improving family welfare from economic aspects in the Baru-Baru Tanga Village, Pangkajene Subdistrict, Pangkep Regency. The results showed that the efforts to empower pond workers in promoting family welfare were beneficial in covering their family's daily needs as well as maintaining and maintaining the family's survival. There are several obstacles faced by farmworkers in improving family welfare, namely lack of business capital, low education, sometimes unsupportive weather and minimal equipment/tools.